The relationship between pre-flight decision-making and cue utilization - Azar, Danielle (2012)
This study examined the relationship between measures of cue utilization and decision selection in the context of pre-flight decision-making. Fifty one licensed pilots participated in an on-line assessment of cue utilization using the program EXPERTise. The results revealed a relationship between cue utilization and decision selection in a pre-flight decision scenario. Overall, the results suggest a role for assessments of cue utilization in the evaluation of pilots’ capacity for effective weather-related decision-making.